Bridging Faith and Innovation: A Review of Social Innovation and Social Value Creation in Faith-Based Philanthropy Organizations - Dinar Apriyanto; FENDY SUHARIADI; Muhammad Miftahussurur (Jurnal Ilmu Multidisiplin, 2025)
This review addresses the challenge Faith-Based Philanthropy Organizations (FBPOs) face in integrating social innovation while demonstrating social value. These organizations must balance their unique religious identity with increasing secular demands for measurable impact. This study's objectives are to map how FBPOs implement social innovation, identify the mechanisms linking faith identity to value creation, and propose an integrated conceptual model. A scoping review methodology was employed, utilizing database searches (including Scopus and Web of Science) followed by a qualitative thematic synthesis. The results indicate that FBPOs engage in all four typologies of social innovation (product, process, position, paradigm), distinctly leveraging "religious capital" (trust, volunteer networks, religious funds) as a key input. This process generates multi-dimensional value, including material and crucial non-material (spiritual/communal) outcomes. The findings conclude that FBPOs operate as hybrid organizations managing competing logics, and a conceptual "Faith-Innovation-Value" (F-I-V) model is proposed, highlighting a critical gap in the measurement of non-material value.